Interbank Withdrawal Protocol (IWP): A Complementary System of Rastin Banking - Bidabad, Bijan; Allahyarifard, Mahmoud (International Journal of Islamic Business & Management, 2019)
Purpose: This paper aims to define a new protocol, whereby brings the required preparations for the bank to collect its claim or its customer’s claim through withdrawal from the debtor’s account in other banks and financial institutions that have signed the protocol.Design: According to this protocol and under central bank supervision, the bank (as owner or attorney of the third party) as claimer of check, promissory note, bill, or a debt initiated by customer's commitment based on collaterals or guarantees, withdraws the claim from the debtor’s accounts in other banks and financial institutions that are members of the protocol through Automatic Clearing House (ACH).Findings: Despite taking collaterals, guarantees, and binding of contracts, executive debt collection process through the legal proceedings is a major challenge that banks, financial institutions, and persons are facing. The legal and execution process of debt collection through collaterals and guarantees are complicated, lengthy, and costly. Interbank Withdrawal Protocol (IWP) solves the problem by proposing a protocol to be accepted by banks to permit withdrawal of the account of the debtor in other banks.Practical implications: It is seen much that a person owes a lot to a person or bank, but s/he deposits her/his money at her/his accounts in other banks. The Interbank Withdrawal Protocol (IWP) is an agreement between banks which permits the bank to collect the debt through online-withdraw from the accounts of the debtor at other banks after depleting the account of the debtor at the agent bank.Social implications: This protocol increases reliance and security upon commitments and provides fast settlement and debt collection without time-consuming judicial process. It also reduces judicial proceedings and execution of active files in courts and consequently related costs.Originality/value: Complementary systems in Rastin Banking have been designed to solve the prevailing problems of banking and financial activities. IWP was designed to provide necessary arrangements for fast, clean debt collection and encashing check and collecting the bill.JEL: L86, L87, G21, G24